2019
DOI: 10.1002/fsn3.849
|View full text |Cite
|
Sign up to set email alerts
|

Amebicidal effects of fenugreek (Trigonella foenum‐graecum) against Acanthamoeba cysts

Abstract: Trigonella foenum‐graecum L. (TF) is known to the public as a chest emollient, mucous expectorant, laxative and is used to prevent maturation of boils and diabetes since ancient times. In this study, we aimed to determine the amebicidal effects against Acanthamoeba cysts. Plant extracts were prepared at concentrations of 1, 2, 4, 8, 16, and 32 mg/ml and were placed in a hemocytometer with cell counts 22 × 106 cell/ml. The fatty acid profiles of TF seeds were determined. Standard Acanthamoeba cysts were added a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To surmount infections induced by the pathogen, plant-derived compounds could be used as an alternative strategy for its treatment. A study has reported the inhibitory effect from the seed of Trigonella foenum-graecum extract on cysts from A. castellanii Kaya et al (2019). Rhizome extract of Curcuma longa and its pure compound, Curcumin, showed anti-microbial activity against A. triangularis trophozoites and cysts (Mitsuwan et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…To surmount infections induced by the pathogen, plant-derived compounds could be used as an alternative strategy for its treatment. A study has reported the inhibitory effect from the seed of Trigonella foenum-graecum extract on cysts from A. castellanii Kaya et al (2019). Rhizome extract of Curcuma longa and its pure compound, Curcumin, showed anti-microbial activity against A. triangularis trophozoites and cysts (Mitsuwan et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative therapeutics have been suggested such as photodynamic chemotherapy (by employing the use of light-sensitive medication and a light source to destroy A. castellanii ) (Ferro et al, 2006), therapeutic corneal cross-linking [by combining ultraviolet light A and riboflavin (B2)] (Khan et al, 2011; Ting et al, 2021c, Said et al, 2021), amniotic membrane transplantation (Ting et al, 2021d), silencing messenger RNA using small interfering RNA (Lorenzo-Morales et al, 2010), and combining nanoparticles with anti- A. castellanii drugs for targeted drug delivery to infection sites (Anwar et al, 2018). In the face of therapeutic inadequacies and potential toxicity, researchers are delving into alternate sources of possible treatment using natural sources which have shown anti-acanthamoebic activity (Dodangeh et al, 2018; Hadas et al, 2017a; Hadas et al, 2017b; Saoudi et al, 2017; Mahboob et al, 2017; Kaynak et al, 2018; Sifaoui et al, 2017; Kaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…castellanii drugs for targeted drug delivery to infection sites (Anwar et al, 2018). In the face of therapeutic inadequacies and potential toxicity, researchers are delving into alternate sources of possible treatment using natural sources which have shown anti-acanthamoebic activity (Dodangeh et al, 2018;Hadas et al, 2017a;Hadas et al, 2017b;Saoudi et al, 2017;Mahboob et al, 2017;Kaynak et al, 2018;Sifaoui et al, 2017;Kaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mature fenugreek seeds contain up to 1.34 % of the amount of steroid saponins (diosgenin, tigonin, yamogenin) and they are used in official medicine in 8 countries [1][2][3].…”
Section: Introductionmentioning
confidence: 99%